Motor Disability and Resilience in University Students - Briones, Marcelo Fabian Barcia; Intriago, Hipatia Alexandra Meza; Ruiz, Marlene Stephanie Lino (International Research Journal of Management, IT & Social Sciences, 2018)
Motor disability is a situation that induces disadvantage in people who suffer from it about healthy people. This situation can be accentuated in the case of university students who must fulfill diverse activities that demand different degrees of physical and mental effort, where the students with motor disability can feel the consequences derived from the disability, with direct influence in the resilience of the students, same. The work shows the results of a study carried out on a group of 35 young people with motor disabilities who study at the Technical University of ManabÃ. Wherein the result of resilience is reflected regarding age, the stage of acquired disability and the degree of it, highlighting the need for the development of psychology activities that favor the strengthening of resilience.